Juvenile-Onset Non-Poikilodermatous CD8+CD56+ Mycosis Fungoides - Thilo Gambichler; Andrea Thiele; Hartmut Merz; Laura Susok; Stefanie Boms (MDPI AG, 2024)
The most frequent primary cutaneous lymphomas observed in childhood and adolescence are mycosis fungoides (MF) and CD30-positive lymphoproliferative diseases. We report a 22-year-old female who presented with a 6-year history of multiple well-demarcated large roundish-oval scaly and reddish-brownish patches and plaques on the trunk and extremities. Histopathology revealed the focal parakeratosis and prominent epidermotropism of atypical lymphocytes, which were positive for CD8, CD56, and TIA-1 and showed a loss of CD7 and CD5 expression. T-cell receptor (TCR) gene rearrangement analysis (multiplex-PCR, BIOMED-2) of the lesional skin demonstrated the rearrangement of the gamma chain (tube A: 162 nt). Based on clinicopathological findings and a complete work-up, she was diagnosed with juvenile non-poikilodermatous C8+/CD56+ MF in stage IA. Resolution of the skin lesions was achieved by 16-week narrowband UVB phototherapy and clobetasol propionate 0.05% ointment. Juvenile-onset non-poikilodermatous CD8+CD56+ MF represents a very rare MF subtype and is associated with an indolent course. In order to avoid too aggressive diagnostics and treatments, clinicians should be aware of this rare and indolent MF variant in childhood and adolescence.